Revision and cladistic analysis of Psalistops Simon, 1889, Trichopelma Simon, 1888 and Cyrtogrammomma Pocock, 1895 (Araneae: Theraphosidae) based on a cladistic analysis of relationships of Theraphosidae, Barychelidae and Paratropididae - Mori, Andre; Bertani, Rogerio (Zootaxa, 2020)
The genera Psalistops Simon, 1889, Trichopelma, Simon, 1888 and Cyrtogrammomma Pocock, 1895 are revised and included in cladistics analyses including almost all species of these genera. In order to test previous morphological hypotheses on the relationships of Barychelidae, Paratropididae and Theraphosidae and because of the controversial taxonomic position of Psalistops and Trichopelma, a set of terminal taxa representing all subfamilies of Paratropididae (Paratropidinae, Glabropelmatinae), Barychelidae (Barychelinae, Sasoninae, Trichopelmatinae) and most theraphosid subfamilies were included, as well as a diplurid, a nemesiid, and a pycnothelid, the later used to root the cladogram. The matrix with 66 terminal taxa, 2 continuous and 93 discrete characters was analysed with TNT 1.5. We found that Trichopelmatinae is not a monophyletic group, and Psalistops is transferred to Theraphosidae, as well as the barychelid genus Cyrtogrammomma and the paratropidid genus Melloina Brignoli. Cyrtogrammomma was retrieved as the sister group of Trichopelma, and Melloina as the sister group of Holothele Karsch. Psalistops was retrieved as the sister group of Reichlingia Rudloff, and the clade with these two genera is the most basal in Theraphosidae. Barychelidae was found to be monophyletic and the sister group of Theraphosidae. Paratropididae was retrieved as the sister group of Barychelidae + Theraphosidae. The relationship and possible synapomorphies of the three families are herein discussed.                This is the first time since Raven (1985) that representatives of all barychelid (Barychelinae, Sasoninae, Trichopelmatinae), paratropidid (Paratropidinae, Glabropelmatinae) and most theraphosid subfamilies have been included in a morphological cladistic analysis.                Psalistops comprises two species, P. melanopygius Simon, 1889 (type species) and P. colombianus sp. nov. Psalistops montigena Simon, 1889, P. tigrinus Simon, 1889 and P. zonatus Simon, 1889 are synonymized with P. melanopygius Simon, 1889. Psalistops fulvus Bryant, 1948, P. hispaniolensis Wunderlich, 1988 (fossil), P. maculosus Bryant, 1948, P. venadensis Valerio, 1986 and P. steini (Simon, 1889) are transferred to Trichopelma. Psalistops gasci Maréchal, 1996 is transferred to Hapalopus Ausserer (Theraphosidae); P. opifex (Simon, 1889) and P. solitarius (Simon, 1889) are transferred to Schismatothele Karsch, 1879 (Theraphosidae). Schismatothele solitarius (Simon, 1889) n. comb. is synonymized with Schismatothele lineata Karsch, 1879, n. syn. Psalistops nigrifemuratus Mello-Leitão, 1939 is probably a nemesiid or pycnothelid, and herein considered as nomen dubium in Pycnothelidae. Trichopelma comprises 22 species: Trichopelma nitidum Simon, 1888 (type species), T. coenobita (Simon, 1889), T. steini (Simon, 1889), T. affine (Simon, 1892), T. cubanum (Simon, 1903), T. maculatum (Banks, 1906), T. zebra (Petrunkevitch, 1925), T. banksia Özdikmen & Demir, 2012, T. insulanum (Petrunkevitch, 1926), T. fulvus (Bryant, 1948) n. comb., T. laselva Valerio, 1986, T. venadensis (Valerio, 1986) n. comb., T. huffi sp. nov., T. gabrieli sp. nov., T. tostoi sp. nov., T. goloboffi sp. nov., T. juventud sp. nov., T. laurae sp. nov., T.bimini sp. nov., T. loui sp. nov., T. platnicki sp. nov., and T. hispaniolensis Wunderlich, 1988 n. comb. (fossil). Trichopelma maculosus (Bryant, 1948) n. comb. is synonymized with P. fulvus Bryant, 1948; T. corozalis (Petrunkevitch, 1929) is synonymized with T. insulanum (Petrunkevitch, 1926). Trichopelma astutum Simon, 1889 is transferred to Euthycaelus Simon, 1889, and T. maddeni Esposito & Agnarsson, 2014 to Holothele Karsch, 1879 (Theraphosidae). Trichopelma flavicomum Simon, 1891 is transferred to Neodiplothele (Barychelidae, Sasoninae). The species T. illetabile Simon, 1888, T. spinosum (Franganillo, 1926), T. scopulatum (Fischel, 1927) and T. eucubanum Özdikmen & Demir, 2012 are considered as nomina dubia. Cyrtogrammomma comprises two species: C. monticola Pocock, 1895 (type species) and C. raveni sp. nov.